2015
DOI: 10.1111/jfs.12177
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibiotic Resistance and Biogenic Amine Production of Lactic Acid Bacteria Isolated from Fermented Turkish Sausage (Sucuk)

Abstract: The aim of this study was to isolate lactic acid bacteria (LAB) from sucuk and to determine their antibiotic resistance and biogenic amine production abilities. A total of 65 presumptive LAB were isolated and they were molecularly identified as Pediococcus acidilactici (47.7%), Enterococcus faecium (36.9%), Lactobacillus sakei ssp. carnosus (4.6%), Lactobacillus sakei ssp. sakei (4.6%), Pediococcus pentosaceus (3.1%), Enterococcus faecalis (1.5%) and Weissella viridescens (1.5%) by sequencing 16S rDNA. The LAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
15
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
(77 reference statements)
10
15
2
2
Order By: Relevance
“…In these studies, the method used for the detection of biogenic amines was a qualitative method using bromocresol purple as a pH indicator. Using this method, E. faecium and E. faecalis were able to produce biogenic amines [110]. The detection of genes encoding amino acid decarboxylase would help to confirm these observations.…”
Section: Biogenic Amine Production Of Weissellasupporting
confidence: 49%
See 1 more Smart Citation
“…In these studies, the method used for the detection of biogenic amines was a qualitative method using bromocresol purple as a pH indicator. Using this method, E. faecium and E. faecalis were able to produce biogenic amines [110]. The detection of genes encoding amino acid decarboxylase would help to confirm these observations.…”
Section: Biogenic Amine Production Of Weissellasupporting
confidence: 49%
“…This ability is highly variable and often strain specific [177]. No production of biogenic amine from histidine, lysine, ornithine or tyrosine has been detected for W. confusa strains [118] neither by W. cibaria strains [178] nor by W. viridescens [110]. In these studies, the method used for the detection of biogenic amines was a qualitative method using bromocresol purple as a pH indicator.…”
Section: Biogenic Amine Production Of Weissellamentioning
confidence: 99%
“…strains (Tuncer, 2009;Komprda et al, 2010;Kalhotka et al, 2012;Inoğlu and Tuncer, 2013). PCR study showed compatibility with the result of the phenotypically tyrosine decarboxylating ability, as confirmed by Inoğlu and Tuncer (2013) and Yüceer and Özden-Tuncer (2015).…”
Section: Discussionmentioning
confidence: 72%
“…Yüceer and Özden Tuncer () report isolation of Pediococcus acidilactici and Pediococcuspentosaceus from almost 50% of uninoculated sukuc samples (a dry, spicy sausage, also named sucuk, sujux, suxhuk, etc. ), suggestive of their technological role, and determined their AMR profiles.…”
Section: Assessmentmentioning
confidence: 99%